Placebo-controlled trial of oral amantadine and zolpidem efficacy on the outcome of patients with acute severe traumatic brain injury and diffuse axonal injury - sajad shafiee; Saeed Ehteshami; Mahmoodd Moosazadeh; Saeed Aghapour; Kaveh Haddadi (Babol University of Medical Sciences, 2022)
Background: A constituent of diffuse axonal injury (DAI) is supposed to be present in about 1/3 of all severe traumatic brain injury (TBI) as specified by pathologic documents. Diffuse axonal injury is categorized by extensive injury to axons in the brain. A rise in the incidences of TBI, and the limited study to verified effect of drugs like amantadine and zolpidem in improving the consciousness levels of patients with acute traumatic brain injury with axonal injury enthused us to initiate this study in the acute TBI patients. Methods: In our randomized, controlled trial involving patients with acute severe TBI, we studied 66 patients in 3 groups. Group 1 (n=22) received oral amantadine, Group 2 (n=22) received oral zolpidem, whereas group 3 (n=22) received placebo, the first 8 days after injury respectively. The primary outcome measures included GCS (Glashow coma scale) through the initial admission, a complete medical history was recorded, and each patient had a meticulous physical and neurological investigation. Results: We found that the administration of amantadine in an acute phase after injury improved the rate of patients GCS and GOS (Glasgow Outcome Scale) compared with zolpidem and placebo groups, but without any significant statistical difference. Conclusion: Our results has emphasized that because amantadine has intense biochemical effects on several ways, it appears to be beneficial in acute period after DAI-associated TBI.